A Systemic Literature Review: Educational Programming Models For Gifted Students in Indonesia - Adi Suseno; Rochmat Wahab (Universitas Negeri Yogyakarta, 2023)
This study presents a systemic literature review that discusses the state of educational programming models for gifted students in Indonesia. The purpose of the study is to give a summary of the current educational programming approaches for gifted students at all academic levels and to depict students who are eligible for educational programming models. This study uses the guidelines of the systemic review process by Newman Gough which consists of several stages. The selected publications for literature study were based on inclusion and exclusion criteria in terms of document type, year of publication, language, and place of research. The results of this literature study provide an overview that (1) most teachers have the same understanding of gifted students who are defined as having a standardized IQ test score above 130, and some schools apply specific additional criteria for students who will receive gifted programs, and ( 2) the model of educational programming that is often used for gifted students is acceleration, either a full-year or grade-skipping acceleration.